2011
DOI: 10.1371/journal.pone.0017472
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Polarised Intestinal Porcine Epithelial Cells to Mycotoxin Deoxynivalenol Depends on the Route of Application

Abstract: Background and AimsDeoxynivalenol (DON) is a Fusarium derived mycotoxin, often occurring on cereals used for human and animal nutrition. The intestine, as prominent barrier for nutritional toxins, has to handle the mycotoxin from the mucosa protected luminal side (apical exposure), as well as already absorbed toxin, reaching the cells from basolateral side via the blood stream. In the present study, the impact of the direction of DON exposure on epithelial cell behaviour and intestinal barrier integrity was el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
110
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(125 citation statements)
references
References 47 publications
15
110
0
Order By: Relevance
“…On the other hand, probably it is not the leading role by Erk1/2 in regulating barrier functions of DON in IPEC-J2 cells. Consistent with the previous study [27], we identified a significant decrease in Erk1/2 phosphorylation, which might enhance the pro-apoptotic effects of DON. What is more, besides Erk1/2, intestinal barrier functions may be regulated by other different types of signaling proteins.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, probably it is not the leading role by Erk1/2 in regulating barrier functions of DON in IPEC-J2 cells. Consistent with the previous study [27], we identified a significant decrease in Erk1/2 phosphorylation, which might enhance the pro-apoptotic effects of DON. What is more, besides Erk1/2, intestinal barrier functions may be regulated by other different types of signaling proteins.…”
Section: Discussionsupporting
confidence: 92%
“…Since DON is a daily food contaminant, as prominent barrier for nutritional toxins [10], the intestine has to regularly handle a high concentration of DON from the luminal side. Since the concentrations of DON treatment to IECs was normally adopted in higher μM range [12,26,27,28,29,30], it appears that sensitivity of intestine is very low (1 µM to 100 µM) [31]. Studies have confirmed that apical application of DON up to 6.75–13.5 μM has no significant effect on TEER and expression of claudin-3, claudin-4 or ZO-1 [12,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In three different human intestinal epithelial cell lines, HT-29, Caco-2 and T84, DON was found to induce a dose-dependent decrease in the TEER [32,62,63,71,72,80]. The same effect was observed in the porcine intestinal epithelial cell lines IPEC-1 and IPEC-J2 [71,81]. Interestingly, IPEC-1 cells showed greater sensitivity to DON compared with Caco-2 [71].…”
Section: Don and Other Tctb Alter Intestinal Barrier Functionmentioning
confidence: 77%
“…A dietary component that is known to affect the intestinal barrier function is the mycotoxin deoxynivalenol (4)(5)(6)(7)(8). Deoxynivalenol is one of the most frequently occurring natural toxins in wheat and wheat-based products and can readily enter the food and feed chain because deoxynivalenol is resistant to processing and heating (9).…”
Section: Introductionmentioning
confidence: 99%